2022
DOI: 10.4103/ijdd.ijdd_36_21
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological adverse events of cancer chemotherapy

Abstract: Introduction: Although newer chemotherapeutic drugs prolong patients’ survival, they cause a myriad of dermatological adverse effects leading to decreased quality of life. Aims and Objectives: The study was undertaken to assess the various cutaneous adverse effects associated with chemotherapeutic drugs. Materials and Methods: A total of 736 diagnosed cancer patients on chemotherapy attending the dermatology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“… 5 Anagen effluvium 22 (30.10%) was the frequently observed cutaneous reaction in our study, similar findings were also seen in the studies in the literature. 3 , 6 , 9 , 10 In our study it was commonly found to be associated with platinum- based regimens. Palmar-plantar erythrodysesthesia 14 (19.94%) also known as hand and foot syndrome was the second most common manifestation in our study.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“… 5 Anagen effluvium 22 (30.10%) was the frequently observed cutaneous reaction in our study, similar findings were also seen in the studies in the literature. 3 , 6 , 9 , 10 In our study it was commonly found to be associated with platinum- based regimens. Palmar-plantar erythrodysesthesia 14 (19.94%) also known as hand and foot syndrome was the second most common manifestation in our study.…”
Section: Discussionsupporting
confidence: 51%
“…Similar findings were also seen in a previous study. 3,10 Certain anticancer drugs inhibit both vascular endothelial growth factor receptor and plateletderived growth which disrupts the normal repair process involving both capillaries and fibroblasts and leads to inflammation which presents as painful symmetric erythema over palms and soles and even blisters in severe cases. 2,5,6 In our study we found common regimens associated with palmar-plantar erythrodysesthesia were Doxorubicin+cyclophosphamide, Carboplatin+ Paclitaxel and Cisplatin+Gemcitabine.…”
Section: Discussionmentioning
confidence: 99%